INTERACTIVE E-MODULE: THE ECONOMIC LEARNING SOLUTIONS IN HIGH SCHOOL DURING THE COVID-19 PANDEMIC - Syahrul Munir; Wahyu Fitrianti; Rizza Megasari (Jurnal Pendidikan Ilmu Sosial, 2022)
The purpose of research and development of this Interactive e-module is to provide a solution for studying Economics in high school in the sub-subject Basic equations of Accounting in online learning during the Covid 19 Pandemic. This interactive e-module research and development activity adopts the Borg Gall (2003) model which consists of 7 stages (needs analysis stage, initial draft development, validity test, draft revision, group trial, and revision stage). The results of research and development show that this Interactive e-module discusses three learning module units containing Economics material with the sub-subject of Basic Accounting Equations which is equipped with several interesting interactive features such as QR Code, music, YouTube videos, quiz applications, and games as support. students learn. This interactive e-module is very appropriate to be used as a solution for learning Economics during the Covid 19 Pandemic.